Estimasi Pengaruh Faktor Internal Bank dan Stabilitas Makroekonomi terhadap Profitabilitas dengan Mediasi Rasio Pembiayaan Bermasalah di PT Bank Muamalat Indonesia - Annisa Siti Fathonah; Dadang Hermawan (Jurnal Maps (Manajemen Perbankan Syariah), 2020)
This study aims to determine and analyze how much influence the bank's internal factors such as Equity, Operational Costs per Operating Income (BOPO), Financing Deposit to Ratio (FDR), Non Performing Financing (NPF) as a mediator and external or macroeconomic factors namely inflation and Gross Domestic Product (GDP) on profitability represented by Return on Assets (ROA) at Bank Muamalat Indonesia for the period 2008-2018. The data used in this research are secondary data obtained from the publication of quarterly financial statements from 2008 to quarter 2 of 2018. The method that used in this research is path analysis with SPSS 20.0 as the analytical tool. The results of the study partially test the hypothesis (t-test), in substructure I shows that the capital variable has a significant negative effect on NPF, BOPO and inflation has a significant positive effect on NPF, FDR and GDP do not significantly influence NPF at Bank Muamalat Indonesia. In substructure II partially, Capital, BOPO, significant negative effect on ROA, FDR and NPF has a significant positive effect on ROA, Inflation and GDP does not significantly influence ROA while simultaneously significantly influencing ROA. Based on the sobel test, capital has a significant effect on ROA through NPF, BOPO has a significant effect on ROA through NPF, FDR has a significant effect on ROA through NPF, Inflation has a significant effect on ROA through NPF, while GDP has no significant effect on ROA through NPF.